Ultrafast rotational motions of supported nanoclusters probed by electron diffraction. Issue 5 (16th May 2019) - Vasileiadis, Thomas; Skountzos, Emmanuel N.; Foster, Dawn; Coleman, Shawn P.; Zahn, Daniela; Krečinić, Faruk; Mavrantzas, Vlasis G.; Palmer, Richard E.; Ernstorfer, Ralph
Abstract : Femtosecond electron diffraction is established as goniometer of ultrafast nanocrystal rotations. Abstract : In crystals, microscopic energy flow is governed by electronic and vibrational excitations. In nanoscale materials, however, translations and rotations of entire nanoparticles represent additional fundamental excitations. The observation of such motions is elusive as most ultrafast techniques are insensitive to motions of the phonons' frame of reference. Here, we study heterostructures of size-selected Au nanoclusters with partial (111) orientation on few-layer graphite with femtosecond electron diffraction. We demonstrate that ultrafast, constrained rotations of nanoclusters, so-called librations, in photo-induced non-equilibrium conditions can be observed separately from vibrational structural dynamics. Molecular dynamics and electron diffraction simulations provide quantitative understanding on librations-induced deviations from the conventional temperature dependence of diffraction patterns. We find that nanocluster librations with a period of ∼20 picoseconds are triggered quasi-impulsively by graphene flexural motions. These ultrafast structural dynamics modulate the Au/C interface and hence are expected to play a key role in energy- and mass-transport at the nanoscale.